Accelerator mass-spectrometr SB RAS - Rastigeev, S.A.; Frolov, A.R.; Goncharov, A.D.; Klyuev, V.F.; Konstantinov, E.S.; Kutnykova, L.A.; Parkhomchuk, V.V.; Petrozhitskii, A.V. (Вопросы атомной науки и техники, 2013)
The accelerator mass spectrometer (AMS) created at BINP SB RAS is installed at CCU “Geochronology of the Cenozoic era” for sample dating by the ¹⁴С isotope and for biomedical applications. The most distinguishing fea-tures of BINP AMS is the use of the middle energy separator of ion beams, the magnesium vapors target as a stripper and time-of-flight telescope with thin films for accurate ion selection. Present status of AMS complex and the results of experiments for radiocarbon concentration measurements in test samples are presented. Створений у ІЯФ СО РАН прискорювальний мас-спектрометр (ПМС) встановлено у ЦКП «Геохронологія кайнозою» для датування зразків по ізотопу ¹⁴С і біомедичних застосувань. Сепаратор іонів на середніх енергіях, мішень на парах магнію в якості обдирної мішені і телескоп тонкоплівкових часопролітних детекторів є відмінними рисами УМЗ ІЯФ для надійної селекції іонів. Представлені поточний стан комплексу УМЗ і результати експериментів з вимірювання концентрації радіовуглецю в тестових зразках. Созданный в ИЯФ СО РАН ускорительный масс-спектрометр (УМС) установлен в ЦКП «Геохронология кайнозоя» для датирования образцов по изотопу ¹⁴С и биомедицинских применений. Сепаратор ионов на средних энергиях, мишень на парах магния в качестве обдирочной мишени и телескоп тонкопленочных времяпролетных детекторов являются отличительными особенностями УМС ИЯФ для надежной селекции ионов. Представлены текущее состояние комплекса УМС и результаты экспериментов по измерению концентрации радиоуглерода в тестовых образцах.